Antimicrobial resistance in dairy slurry tanks: A critical point for measurement and control. (November 2022) - Baker, Michelle; Williams, Alexander D.; Hooton, Steven P.T.; Helliwell, Richard; King, Elizabeth; Dodsworth, Thomas; María Baena-Nogueras, Rosa; Warry, Andrew; Ortori, Catherine A.; Todman, Henry; Gray-Hammerton, Charlotte J.; Pritchard, Alexander C.W.; et al.
Abstract: Waste from dairy production is one of the largest sources of contamination from antimicrobial resistant bacteria (ARB) and genes (ARGs) in many parts of the world. However, studies to date do not provide necessary evidence to inform antimicrobial resistance (AMR) countermeasures. We undertook a detailed, interdisciplinary, longitudinal analysis of dairy slurry waste. The slurry contained a population of ARB and ARGs, with resistances to current, historical and never-used on-farm antibiotics; resistances were associated with Gram-negative and Gram-positive bacteria and mobile elements (IS Ecp1, Tn 916, Tn 21 -family transposons). Modelling and experimental work suggested that these populations are in dynamic equilibrium, with microbial death balanced by fresh input. Consequently, storing slurry without further waste input for at least 60 days was predicted to reduce ARB spread onto land, with > 99 % reduction in cephalosporin resistant Escherichia coli . The model also indicated that for farms with low antibiotic use, further reductions are unlikely to reduce AMR further. We conclude that the slurry tank is a critical point for measurement and control of AMR, and that actions to limit the spread of AMR from dairy waste should combine responsible antibiotic use, including low total quantity, avoidance of human critical antibiotics, and choosing antibiotics with shorter half-lives, coupled with appropriate slurry storage.